(untitled) (Journal Of Educational and Psychological Researches, 2018)
Abstract dr.natik@yahoo.com Background: Acute Traumatic Stress Disorder (ATSD) might be complicated by Post Traumatic Stress Disorder (PTSD). Psychological First Aid (PFA) said to be helpful to reduce the possibility of reduction of ASD and PTSD symptoms. PFA is simple procedure to deliver help & support to victims, may be by some one close to him, quietly and professionally. Iraq has and is still experiencing, continuous traumatic stresses. ATSD is especially seen in war such as during the Gulf War, Embargo and nowadays under the current American occupation. With the extreme shortage of recourses and the given late priority to psychological problems and intervention have disastrous consequences on the psycho-social wellbeing of people. Aims: To construct: 1. ATSD Scale (ATSDS) and 2. PFA Program (PFAP) to be used by careers. Using the null hypothesis, it was expected that there will not be significant reduction in ATSD symptoms after the implementation of PFAP. Methods: ATSD Scale was constructed using a 256 population from of both sexes with an age range 15-54 years. Diagnosis based upon DSM-IV criteria for ATSD classification. 10 female patients (23-54) year were treated individually by debriefing as part of the PFAP. Suitable and randomly referred patients were treated over; 12 biweekly sessions, for 45 minutes each session for the period from June 2003- September 03. Outcome: Both ATSD and ATSDP proved to be valid and reliable. Using Will- Coxon’s Rank Signal Test; PFAP for ATSD was effective in reducing the ATSD symptoms significantly. This result was compatible with the literature. Further studies are recommended to use; larger samples and a follow up period, as well as application of PFAP in group setting might prove to be more cost effective in massive traumatic crises and casualties like war. Keys: Acute, Aid, Debriefing, Disorder, First, Iraq, Post, Psychological, Stress, Traumatic, Treatment, War.